2008
DOI: 10.1007/s00262-008-0584-4
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PGE2 enzymatic pathways in cervical (pre)neoplastic lesions and functional consequences for antigen-presenting cells

Abstract: Although human papillomavirus (HPV) DNA is detected in the majority of squamous intraepithelial lesions (SIL) and carcinoma (SCC) of the uterine cervix, the persistence or progression of cervical lesions suggest that viral antigens are not adequately presented to the immune system. This hypothesis is reinforced by the observation that most SIL show quantitative and functional alterations of Langerhans cells (LC). The aim of this study was to determine whether prostaglandins (PG) may affect LC density in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…Previous results have demonstrated that a high epithelial expression of PGE 2 enzymatic pathways (COX-2 and mPGES-1) is correlated with a lower density of LC in cervical (pre)neoplastic lesions [16]. In agreement with these results, the conditioned media of HPV16 VLP-incubated keratinocytes contained higher levels of PGE 2 than those from untreated keratinocytes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Previous results have demonstrated that a high epithelial expression of PGE 2 enzymatic pathways (COX-2 and mPGES-1) is correlated with a lower density of LC in cervical (pre)neoplastic lesions [16]. In agreement with these results, the conditioned media of HPV16 VLP-incubated keratinocytes contained higher levels of PGE 2 than those from untreated keratinocytes.…”
Section: Discussionsupporting
confidence: 83%
“…One random field was counted per well using an eyepiece with a calibrated grid to evaluate the number of fully migrated cells. PGE 2 radioimmunoassay PGE 2 was detected in supernatants of keratinocytes treated or not by VLP according to a previously described RIA [16] using a polyclonal rabbit antiserum, which does not cross react with other prostanoids (thromboxane B2 (TxB 2 ), 6-keto-PGF1a, PGA 2 ) or fatty acids (arachidonic, linoleic, oleic).…”
Section: Chemotaxis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…15 Briefly, paraffin sections were deparaffinized, rehydrated in graded alcohols, and antigens were retrieved in EDTA or in citrate buffer, whereas frozen sections were fixed with 4% paraformaldehyde and nonspecific binding sites were blocked by a 2% BSA solution. Antibodies anti-p63 (clone 7JUL; Novocastra, Newcastle, UK) recognizing all p63 isoforms, anti-Snail (Abcam, Cambridge, UK), and anti-Slug (Abcam) were used for the primary reaction.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…One important mechanism by which tumor-derived PGE 2 suppresses immune responses is the induction of APC dysfunction in vivo resulting in an inhibition of T cell responses against the tumor. This has been demonstrated for human epithelial cancers such as head and neck and cervical cancer (31,32). Several mechanisms by which PGE 2 -induced tolerogenic DCs prevent tumoricidal immune reactions have been discovered: they promote T helper type 2 (Th2) instead of T helper type 1 (Th1) responses and they attract regulatory T cells (33).…”
Section: Discussionmentioning
confidence: 99%